Digital Financial Education for Economic and Financial Inclusion in Vulnerable Sectors of Peru - ORTIZ, Neptalí Rojas; TORRES, Joél Vásquez; RODRÍGUEZ, Víctor Hugo Puican (Theoretical and Practical Research in Economic Fields, 2024)
The study explores the influence of digital financial education on the financial inclusion of workers in the construction sector in Peru. A quantitative approach with a non-experimental and cross-sectional design was used, applying a questionnaire to 128 self-employed workers. The results indicate a moderate influence of digital financial education on financial inclusion, with an R value of 0.541 and an R² of 0.292. The ANOVA analysis and the regression coefficients confirm the significance of the model (p < 0.001). Factors such as perception and trust in digital banking and integration of emerging technologies significantly influence financial inclusion. Most workers have a good level of digital financial literacy, although there is a need to improve training in digital tools; revealing that digital financial literacy is crucial for financial inclusion and sustainable economic growth, fulfilling Sustainable Development Goal 8.